"Beatissimo Padre ... sono rientrato dalla Terra Santa" Il rapporto a Pio xii di mons. Giuseppe Bicchierai sulla situazione in Palestina e Israele agli inizi del 1949 - D'Angelo, Augusto (Studi e materiali di storia delle religioni, 2019)
The months following the birth of the State of Israel, on the eve of its first elections (25 January 1949), a priest from Milan went on pilgrimage to Palestine. He visited the Arab part of Jerusalem and Bethlehem and met with ecclesiastical personalities as well as with Italian diplomats. On his return, he wrote a report, which was sent to Pius xii. Msgr. Giuseppe Bicchierai's travels and encounters in the Holy Land are shedding light on his still unknown activities. Furthermore, they are adding elements on the modalities the Holy See was informed the early years after wwii about the evolution of the situation in Palestine after the birth of the State of Israel and the whole Middle East.